Keberadaan Tari Salapan Di Kenagarian Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat - Ranti Lestari; Fuji Astuti (FBS Universitas Negeri Padang, 2019)
The research aims to reveal and describe the existence of the Salapan dance in enagarian Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat. This type of research is qualitative research with a descriptive method. This type of research uses primary and secondary data. The main instrument in this research is its own researchers and assisted with supporting instruments such as stationery and cameras. Data collection techniques are conducted by way of library studies, observations, interviews and documentation. The steps for analyzing data are data collection, classifying data, analyzing data, interpreting data and making conclusions. The results showed that the existence of the Salapan dance in the middle of society is no longer exist because this dance is rarely displayed and there is no workshop to defend this dance. The choreographers of the Salapan dance creations have also eliminated the meaning of the tradition of dance by changing the movements and properties of the dance itself. The Salapan dance is no longer displayed at events held by local communities such as weddings, but the Salapan dance is only shown more frequently at the request of Tourism office in West Pasaman and competition events.